Islamic Leadership Management in Pesantren - Puspita, Amelia Tri (The Economic Review of Pesantren, 2024)
Many concepts of management and leadership have changed. In the Islamic concept, leadership is a concept of interaction, relationship, authority process, influencing, directing and coordinating activities both horizontally and vertically. Then, in management theories, the leader's function is as a planner and decision maker (planning and decision maker), organization (organization). Leadership and motivation (leading and motivation), supervision (controlling) and others. In any view, everything must be done neatly, correctly, orderly, and regularly. The processes must be followed properly. This research aims to examine more deeply the practices of Islamic leadership management in Islamic boarding schools. This study has at least two objectives: (1) mapping studies related to Islamic leadership management in general; (2) elaborating on the Islamic leadership concept at Pesantren. The results showed that the leadership style adopted by the Kiai greatly influences the educational environment, both in terms of academics and morals of the students. Therefore, the relationship between Islamic leadership and the success of Islamic boarding school management is very important, because it directly influences educational outcomes, organizational culture, and the overall effectiveness of these institutions.